A Review of Kukadi Canal Irrigation Project (Journal of Advances and Scholarly Researches in Allied Education, 2021)
One major hydraulic project that exemplifies the importance of water management in agricultural growth is the Kukadi Canal Irrigation Project. Located in an area rich in agricultural history, this initiative seeks to improve water distribution, increase crop yields, and strengthen local economies. Our investigation into this evaluation takes us through the beginnings of the project, its complex engineering, its effects on nearby communities, & its overall value to sustainable agriculture. By delving into the Kukadi Canal Irrigation Project, one may learn a great deal about the interdependent nature of water resource management and agricultural success, as well as about the complex web of engineering, ecology, and socioeconomic factors at play. The Kukadi Canal Irrigation Project is reviewed in this paper..